Professor Grażyna Grelowska - Kozaczka, Eugeniusz; Drycz, Czesław (Archives of Acoustics, 2022)
We write these words with great sadness and regret, feelings caused by the loss of such a special person as Professor Grazyna Grelowska was. Our memories and thanks for the gift of acquaintance, friendship, and the possibility of working together provide evidence of that what united us and made us focus on the issues of science and the effort to explore the surrounding world, and more specifically – the sea depths and the sound propagating in water, acoustics, and hydroacoustics.